Perlindungan Hukum Para Pihak dalam Suatu Kredit Perbankan Akibat Penyebaran Covid-19 Dikategorikan Sebagai Keadaan Memaksa - Achmad Akbar Santosa Mulyadi; Sabir Alwy; Nurfaidah Said (Universitas Medan Area, 2022)
The purpose of this study is to interpret legal protection for parties in a banking credit as a result of the COVID-19 pandemic which is categorized as force majeure or overmacht. The research that the author uses is a normative research type, normative research is a type or type of research that focuses on written studies that use secondary data such as legislation, court decisions, legal theory, legal principles, legal principles and can be in the form of scientific works. by law scholars, so this research is closely related to library research. The approach in this research is to use a statutory approach and a conceptual approach. The results of the research on legal protection for banking credit during the COVID-19 pandemic initially by assessing its scope, that it can be categorized as an unnatural situation or condition, special circumstances that are immediate and short-lived and from the conditions experienced now give birth to policies or regulations government to contain the spread of COVID-19. Apart from that, it also includes types of conditions that are subjective or relative, the main impact of which is on health and economic conditions, which are subjective conditions that cause difficulties in carrying out obligations for debtors.